Invitación a la lengua siriaca - Kiraz, George Anton (Gorgias Handbooks, 2022)
"A Spanish translation of George Kiraz's popular New Syriac Primer. This fruitful integration of scholarly introduction and practical application provides a primer that is more than a simple grammar or syntactic introduction to the language. Written in a style designed for beginners, Kiraz avoids technical language and strives for a reader-friendly inductive approach"--